Trend in seroprevalence of Hepatitis B virus infection among blood donors of coastal Karnataka, India - Karandeep Singh; Sudha Bhat; Shamee Shastry (Journal of Infection in Developing Countries)
Background: Hepatitis B is one of the transfusion transmissible infections. The prevalence of this infection varies across the different geographies. Noting the trend in seroprevalence is useful to assist the preventive strategies. The aim of this study was to determine the trend of seroprevalence of hepatitis B in costal Karnataka over a three-year period. Methodology: The study was conducted at the blood bank of a tertiary care hospital serving predominantly the people of coastal Karnataka. A retrospective analysis of blood donors over a period of three years was done to assess the seroprevalence and the trend of hepatitis B infection. ELISA was used to detect the hepatitis B surface antigen in the donors as a marker of infection. Results: A total of 30,428 blood donors were studied. 189 (0.62%) were positive, which comes under the “low prevalence ( < 2%) zone” per World Health Organization (WHO) guidelines. A decreasing trend over three years was seen. Replacement donors and male blood donors showed higher seropositivity compared to voluntary donors and female donors. Chi-square test was used to calculate the significance of difference between the groups. Conclusion: Coastal Karnataka has a low prevalence of hepatitis B in blood donors with a decreasing trend over the last three-year period.